Contact Phonology : Fonologi Kata Serapan dalam Bahasa Jepang - I Gede Oeinada (Journal Social and Humaniora, 2018)
This paper focuses its discussion about loanword phonology in Japanese language. Loanword phonology is one of five contact phonology situations that was described by Smith (2007). The four other situations are areal influence, dialect mixing, language mixing, and simplification. Japanese language has been borrowing many words from foreign languages. One of those foreign languages is English. As we all know that both languages, Japanese and English, have different phonological system. Therefore, borrowed words of English language has been adapted to fit the phonological patterns of Japanese language. This adaptation could solve the loanword phonology problem. And because up until now the number of loanword in Japanese language is till limited so the phonological system of Japanese language is remain unaffected. In other words, the loadwords’ phonology does not cause lasting changes in the phonological system of Japanese language.